EVALUATION OF THE CREATIVITY ACTIVITY SERVICE (CAS) PROGRAM AT A PRIVATE INTERNATIONAL BACCALAUREATE SCHOOL USING STAKE’S EVALUATION MODEL - Sibarani, Debora Pratiwi (Polyglot, 2024)
Creativity Action Service (CAS) is one of the Diploma Program requirements in the International Baccalaureate (IB) curriculum for students in grade 11 and 12. Through this CAS program, students are expected to grow in awareness of their own strengths and potential, learn to overcome the challenges from new activities they have initiated and planned, work collaboratively, show persistence and commitment to be involved in global issues. Periodic evaluation of the program in IB curriculum schools is necessary to investigate the quality of the program and its components which can be used for assessment and decision making towards the improvement and/or accountability of the program. The evaluation result also contributes to increased organizational and social values not only for the school itself, but also for the community affected by this program. This evaluation research uses a descriptive qualitative method by implementing the Countenance Stake evaluation model that emphasizes descriptions and judgments to see the objective conditions at the antecedent (context), transaction (process), and outcome (result) stages. Data collection was carried out through documentation studies, interviews with CAS coordinators, teachers as CAS advisors, students, as well as observing the program implementation. The evaluation results were analyzed and categorized as best practices, challenges, and support systems which in the end became suggestions for improvements in short-term, medium-term, and long-term implementation strategies for the school.Bahasa Indonesia AbstrakBerkenaan dengan fakta bahwa pembelajaran penulisan Bahasa Inggris sering dianggap sebagai aktivitas individual, budaya menulis kolaboratif memegang sebuah peranan penting untuk meningkatkan motivasi menulis pelajar Bahasa Inggris di seluruh dunia yang dapat membawa mereka menjadi penulis optimis, inovatif, dan cakap. Studi pustaka skala kecil ini diperuntukan secara mendalam untuk menyelidiki apakah budaya menulis kolaboratif dapat tumbuh dengan dukungan Google Docs. Oleh karena itu, peneliti dengan sangat kritis meninjau hasil penelitian yang telah dihasilkan oleh 20 penelitian menulis kolaboratif dan Google Docs dengan bantuan dari analisis tematik. Metode analisis tematik diterapkan untuk memastikan kredibilitas, kepercayaan, dan keandalan dari setiap hasil penelitian yang telah dikelompokan secara spesifik. Untuk menghasilan hasil penelitian yang relevan dan kontekstual, peneliti memilih penelitian menulis kolaboratif dan Google Docs dari tahun 2019 hingga 2023. Berkenaan dengan hasil penelitian yang telah didapat, instruktur menulis Bahasa Inggris di seluruh dunia disarankan untuk menggabungkan penerapan strategi menulis kolaboratif dengan Google Docs agar secara terus menerus mentransformasi pelajar Bahasa Inggris menjadi penulis seumur hidup yang lebih kolaboratif, tangguh, dan ulet.